Plane strain deformation in a thermoelastic microelongated solid with internal heat source - Ailawalia, Praveen; Sachdeva, Sunil Kumar; Pathania, Devinder Singh (Zielona Góra: Uniwersytet Zielonogórski)
The purpose of this paper is to study the two dimensional deformation due to an internal heat source in a thermoelastic microelongated solid. A mechanical force is applied along an overlaying elastic layer of thickness h. The normal mode analysis has been applied to obtain the exact expressions for the displacement component, force stress, temperature distribution and microelongation. The effect of the internal heat source on the displacement component, force stress, temperature distribution and microelongation has been depicted graphically for Green-Lindsay (GL) theory of thermoelasticity.
Keywords: thermoelasticity; microelongation; heat source; normal mode analysis